2021
DOI: 10.1186/s12873-020-00399-8
|View full text |Cite
|
Sign up to set email alerts
|

Increasing consultant-level staffing as a proportion of overall physician coverage improves emergency department length of stay targets

Abstract: Objectives One goal of Emergency Department (ED) operations is achieving an overall length of stay (LOS) that is less than four hours. The goal of the current study was to assess for association between increasing number of on-duty EM Consultants and LOS, while adjusting for overall (all-grade) on-duty emergency doctors’ numbers and other operational factors. Methods This was a retrospective analysis of three years (2016–2019) of data, employing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…These influential factors were accounted due to the fact that previous studies have shown that adjusting for patient churn increases nurse staffing across all units and shifts [ 36 ]. Increasing number of on-duty health care personnel [ 5 ] or a higher number of night-time staffing [ 9 ] were also assumed to shorten the length of stay. Earlier, an increase in the NPR were shown to reduce the length of stay [ 18 ], although we did not find this effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These influential factors were accounted due to the fact that previous studies have shown that adjusting for patient churn increases nurse staffing across all units and shifts [ 36 ]. Increasing number of on-duty health care personnel [ 5 ] or a higher number of night-time staffing [ 9 ] were also assumed to shorten the length of stay. Earlier, an increase in the NPR were shown to reduce the length of stay [ 18 ], although we did not find this effect.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, length of stay is an important indicator of the efficiency of hospital management [ 3 , 4 ]. Increasing number of on-duty health care personnel may shorten the length of stay [ 5 ], and higher average working hours per patient day have predicted shorter length of in-hospital stay [ 6 ]. A greater number of working hours per patient day has been shown to be linked with shorter length of stay also in Finland [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 One factor in longer ED LOS is inefficient subspecialty consultation—awaiting consultation is associated with a prolonged inpatient stay, and conversely increasing consultant staffing may reduce LOS. 3 An essential part of the consultation is 2‐way communication. Although modern electronic health records (EHRs) allow consults to be requested via order, 2‐way communication is nonetheless helpful to framing and resolving the consult question.…”
Section: Introductionmentioning
confidence: 99%
“…Increased length of stay (LOS) in the ED is associated with increased mortality, medical errors, delays in care, and decreased quality of care 1,2 . One factor in longer ED LOS is inefficient subspecialty consultation—awaiting consultation is associated with a prolonged inpatient stay, and conversely increasing consultant staffing may reduce LOS 3 . An essential part of the consultation is 2‐way communication.…”
Section: Introductionmentioning
confidence: 99%